A global view on cancer incidence and national levels of the human development index. Issue 11 (30th August 2016) - Fidler, Miranda M.; Soerjomataram, Isabelle; Bray, Freddie
Abstract : Socioeconomic factors are associated with cancer incidence through complex and variable pathways. We assessed cancer incidence for all cancers combined and 27 major types according to national human development levels. Using GLOBOCAN data for 184 countries, age‐standardized incidence rates (ASRs) were assessed by four levels (low, medium, high, very high) of the Human Development Index (HDI), a composite index of life expectancy, education, and gross national income. A strong positive relationship between overall cancer incidence and HDI level was observed. When comparing the ASR in very high HDI regions with that in low HDI regions, we observed a positive association ranging from 2 to 14 and 2 to 11 times higher in males and females, respectively, depending on the cancer type. Positive dose–response relationships between the ASR and HDI level were observed in both sexes for the following cancer types: lung, pancreas, leukemia, gallbladder, colorectum, brain/nervous system, kidney, multiple myeloma, and thyroid. Positive associations were also observed for testicular, bladder, lip/oral cavity, and other pharyngeal cancers, Hodgkin lymphoma, and melanoma of the skin in males, and corpus uteri, breast, and ovarian cancers and non‐Hodgkin lymphoma in females. A negative dose–response relationship was observed for cervical and other pharyngeal cancers and Kaposi sarcoma in females. Although the relationship between incidence and the HDI remained when assessed at the country‐specific level, variations in risk within HDI levels were also observed. We highlight positive and negative associations between incidence and human development for most cancers, which will aid the planning of cancer control priorities among countries undergoing human development transitions. Abstract : What's new? Societal and economic advancements, which lead to lifestyle changes and the development of more technologically complex human environments, have profound effects on the scale and profile of cancer. This global assessment of the link between national human development and the incidence of 27 cancer types reveals differing cancer profiles across levels of the Human Development Index, with marked risk gradients observed for specific cancers. In particular, cancers associated with westernization and socioeconomic advancement are displacing infection‐related cancers worldwide. These findings offer insight into human development‐related cancer incidence and the future global cancer burden, and could facilitate cancer control planning in countries experiencing socioeconomic change.